Diachronic Study of Coastal Vegetation Cover in Al Hoceima (Morocco): A Geospatial Analysis Using Remote Sensing and GIS - Mouddou Alae; Taher Morad; Etebaai Issam (E3S Web of Conferences, 2024)
Coastal ecosystems are vital land-sea interfaces that are necessary to sustain environmental stability and biodiversity. In many places, the complex network of vegetation cover serves as an essential buffer, preventing erosion, sustaining a variety of habitats, and enhancing ecological resilience overall The study utilizes advanced technologies like GIS, remote sensing, and Landsat images to analyze vegetation changes in Sfiha and Swani's coastal regions over the past 18 years, aiming to understand the impact of land use, climate fluctuations, and human activities on the landscape, Sophisticated remote sensing technology, Landsat satellite images, and Geographic Information System (GIS) tools are among the materials employed. During the designated period, the proportions of changes in the plant cover in the research area are determined and interpreted with the help of these resources. The study reveals significant changes in vegetation cover in Sfiha and Swani, revealing patterns of 21% (2003), 25% (2010), 33% (2015), and 15% (2021), providing insight into the temporal evolution of the coastal ecosystem and influencing conservation strategies and sustainable management practices. This study underscores the broader relevance of employing advanced spatial technologies for the monitoring and management of coastal ecosystems.Introduction